Functionalization of diazotetronic acid and application in a stereoselective modular synthesis of pulvinone, aspulvinones A–E, G, Q and their analogues. Issue 34 (15th August 2018) - Manchoju, Amarender; Annadate, Ritesh A.; Desquien, Lise; Pansare, Sunil V.
Abstract : Diastereoselective aldol condensation of diazotetronic acid and a subsequent arene C–H insertion provides an efficient route to the aspulvinone motif. Abstract : A modular synthesis of aspulvinones A, B, C, D, E, G and the recently isolated aspulvinone Q was developed. The methodology features a highly stereoselective aldol condensation of diazotetronic acid with aldehydes to provide 5-arylidene diazotetronates. Subsequent catalytic intermolecular C–H insertion reactions of the arylidene tetronates with arenes provide a series of naturally occurring aspulvinones including aspulvinones C, D and Q which have not been synthesized before. Variation of the aldehyde and the arene components furnishes synthetic analogues of the aspulvinones.